GOOD CORPORATE GOVERNANCE DAN SUSTAINABLE BUSINESS PRACTICE PERUSAHAAN PUBLIK DI INDONESIA - Dewi, Luh Gede Krisna; Penindra, I Made Dwi Budiana; Setiawan, Putu Ery (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.08.TAHUN.2024, 2024)
This research aims to analyze the influence of good corporate governance mechanisms on environmental investment. Good corporate governance is proxied by the size of the board of commissioners, independent commissioners, institutional ownership and audit committee. Environmental investment is proxied with a PROPER rating that reflects the company's commitment to sustainability . This research uses a sample of non-financial sector companies on the Indonesia Stock Exchange during the period 2015 to 2021. The number of observations in this research is 220 firm years. The data used comes from annual reports and sustainability reports, and is then analyzed using panel data regression techniques and processed using the Eviews 12 tool. The research has succeeded in proving that institutional ownership structure influences the company's level of environmental investment as a form of sustainable business practice. The research found no influence between the size of the board of commissioners, the presence of independent commissioners, managerial ownership and the audit committee as corporate governance components that influence the company's environmental investment level. The research results prove that institutional stakeholder pressure factors influence sustainable business practices and support stakeholder theory. Practically, the findings of this research have implications for drafting better regulations because pressure from institutional stakeholders has a positive impact on sustainable business practices.